Integrating intercultural competence in foreign language teaching: sources, strategies and perspectives - Yakubova, Madina (The Lingua Spectrum, 2025)
This article is devoted to the study of various sources of materials that contribute to the development of intercultural communicative competence (ICC), as well as methodological approaches to their use in the classroom. The paper discusses authentic and didactic resources, digital platforms, project activities and simulations aimed at creating conditions for cultural dialogue. Special attention is paid to methodological strategies that ensure effective implementation of the intercultural component in the educational process. The article provides practical examples of resource use, as well as substantiates the principles of selecting and adapting materials in accordance with the goals of ICC formation.